Interannual variability in thermal state of the upper mixed layer in the Bering Sea in winter - V. A. Luchin (Известия ТИНРО, 2023)
Year-to-year variations of temperature in the upper mixed layer are considered for the ice-free waters of the Bering Sea in cold season (from December to March) using all data of the deep-sea oceanographic observations available to date (12,430 stations for the period from 1943 to 2022). Series of annual mean ﬁelds of the mixed layer temperature in December-March were decomposed by applying the empirical orthogonal function (EOF); dynamics of the ﬁrst two components of decomposition (described in sum 50.4 % of the initial ﬁelds variability) are analyzed. The ﬁrst component (32.4 % of variation) indicates synchronous oscillations over the entire sea area with the maximum contribution at the continental slope. The second component (18.0 % of variance) reﬂects opposite oscillations in two vast regions of the sea located along the continental slope from Cape Navarin to Alaska Peninsula and in the western, central and southern parts of the deep basin. The following statistically signiﬁcant periodic oscillations are revealed by spectral analysis: quasi-biennial and those with periods of 4, 7, and 17–20 year for the 1st EOF and quasi-biennial and those with periods of 3 and 4 year for the 2nd EOF. A statistically signiﬁcant linear trend to warming is detected for the time coefﬁcient of the 1st EOF in the period of 1958–2022. Approximation of this coefﬁcient dynamics with 6-degree polynomial function (polynomial trend) shows a tendencies to the mixed layer cooling in winters of 1969–1972 and 1992–2004 but the opposite tendencies to warming in 1973–1991 and 2005–2022. Variations of time coefﬁcient for the 2nd EOF correspond to opposite tendencies in the areas with positive and negative values of this EOF. For the period from 1958 to 2022, winters in the Bering Sea are classiﬁed by the mixed layer temperature, taking into account the contribution of the 1st EOF only, as «warm» (1958, 1959, 1963, 1964, 1966, 1979, 1982, 1985, 1987, 1997, 2001, 2003, 2004, 2015–2018, 2020, and 2022), «normal» (1960–1962, 1965, 1967, 1968, 1970, 1971, 1974, 1978, 1980, 1981, 1983, 1986, 1989–1994, 1996, 1998, 2005–2007, 2011, 2013, 2014, 2019, and 2021), «cold» (1969, 1972, 1973, 1975–1977, 1984, 1988, 1995, 1999, 2000, 2002, 2008, and 2010), and extremely cold (2009 and 2012).